Human Capital for a Knowledge Society Higher Education in the Maldives : An Evolving Seascape - World Bank (World Bank, 2012)
The Republic of Maldives, a middle-income country of extraordinary natural beauty, is one of the most advanced nations in South Asia. The Maldives consists of an archipelago of nearly 1,200 islands and a population of approximately 400,000 inhabitants; 310,000 Maldivians and 90,000 expatriate workers. More than 25 percent of the populations live in Male, the capital, while the rest are distributed among just under 200 other inhabited islands. The Maldives had attained a gross national income (GNI) per capita of USD 5,790 in 2010. This was the highest among countries in the South Asia region. The country ranked 107th in the human development index (HDI) for 2010, which was the second highest HDI rank in South Asia after Sri Lanka. The Maldives also had the second best position among South Asian countries, after Pakistan, in the doing business indicators in 2010, at 85th in the world. The Government of Maldives (GOM) is seeking to accelerate human development and economic prosperity within the political framework of a modern liberal democracy. The government's reform program to achieve this goal, outlined in the policy statement 'the other Maldives [GOM (2009a)]' contains five pillars: good governance to strengthen democratic institutions and processes; expansion and development of human capital; climate change and adaptation; public sector reform to streamline the delivery of services and improve efficiency; and macroeconomic reform to promote private-sector led growth.